Investigation of the Refining Step of Biodiesel Production - Karaosmanoǧlu, Filiz; Cıǧızoǧlu, K. Barış; Tüter, Melek; Ertekin, Serap (American Chemical Society (ACS), 1996)
The ester product of the vegetable oil−alcohol transesterification reaction (biodiesel) is the best and the most popular diesel fuel alternative. The refining of the transesterification reaction products is technically difficult and brings an extra cost. Also, the purity level of the biodiesel must conform to European Union standards for alternative diesel fuels. The target of this study was to investigate the refining of the product mixture obtained by the transesterification reaction (with an alkali catalyst) of neutralized rapeseed oil (extracted from the seeds of the rape plant cultivated in the Thrace region of Turkey) with methanol. To obtain pure biodiesel conformable to the standards, methods of washing with hot distilled water, dissolving in petroleum ether and then washing with distilled water, and neutralization with H2SO4 (1:1) were tested in the refining step. Washing with hot distilled water at 50 °C was chosen as the best refining process. The purity of the biodiesel obtained was about 99%.